Acinar autolysis and mucous extravasation in human sublingual glands: a microscopic postmortem study - Luciana Reis AZEVEDO-ALANIS; Elen de Souza TOLENTINO; Gerson Francisco de ASSIS; Tânia Mary CESTARI; Vanessa Soares LARA; José Humberto DAMANTE (University of São Paulo, 2015)
Although some morphological investigations on aged human sublingual glands (HSG) found eventual phenomena identified as autolysis and mucous extravasation, the exact meaning of these findings has not been elucidated.Objective The aim of this work is to investigate whether acinar autolysis and mucous extravasation are related to the aging process in human sublingual glands. We also speculate if autolytic changes may assist forensic pathologists in determining time of death.Material and Methods 186 cadavers' glands were allocated to age groups: I (0-30 years); II (31-60), and III (61-90). Time and mode of death were also recorded. Acinar autolysis and mucous extravasation were classified as present or absent. Ultrastructural analysis was performed using transmission electron microscopy (TEM). Data were compared using Mann-Whitney U, Spearman's correlation coefficient, Kruskal-Wallis, and Dunn tests (p<0.05).Results There was correlation between age and acinar autolysis (r=0.38; p=0.0001). However, there was no correlation between autolysis and time of death. No differences were observed between genders. TEM showed mucous and serous cells presenting nuclear and membrane alterations and mucous cells were more susceptible to autolysis.Conclusion Acinar autolysis occurred in all age groups and increased with age while mucous extravasation was rarely found. Both findings are independent. Autolysis degrees in HSG could not be used to determine time of death.